1995
DOI: 10.1136/hrt.74.2.186
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of right ventricular regional contraction and comparison with the left ventricle in normal humans: a cine magnetic resonance study with presaturation myocardial tagging.

Abstract: Objective-Right ventricular regional contractility has been thought to be difficult to assess precisely. Cine magnetic resonance imaging with presaturation myocardial tagging was employed to quantitate the contraction of the right ventricular free wall and to identify normal performance compared with the left ventricle. Methods-Nine normal volunteers, aged 27-39 years, were examined in a 1 5 Tesla superconductive magnet, and short axis and four-chamber sections at the midventricular level were imaged with cine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 20 publications
5
44
0
1
Order By: Relevance
“…Differences between left and right heart measurements might be caused by different dispersion of longitudinal and circular myocardial fibers (7). In agreement with this, values have been found higher in the right than in the left heart in this study, in children (6) and in adults (14).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Differences between left and right heart measurements might be caused by different dispersion of longitudinal and circular myocardial fibers (7). In agreement with this, values have been found higher in the right than in the left heart in this study, in children (6) and in adults (14).…”
Section: Discussionsupporting
confidence: 80%
“…Two right ventricle walls have been studied in children (6). The right superior wall to our knowledge has not been assessed by ultrasound earlier, but contraction in these segments has been assessed by MRI (7,8) in adults. Three segments (basal, mid, and apical) are usually studied in each wall.…”
Section: Methodsmentioning
confidence: 99%
“…They determined the longitudinal strain of the left lateral wall as -26 11%, the interventricular septum as -24 8%, and the lateral right ventricular wall as 45 13%; they concluded that the longitudinal strain of the right ventricle was larger than that of the left ventricle. Using TTS, we observed increased longitudinal strain of the right ventricle compared to the left ventricle (-46 9%, data not shown), and this likely reflects the longitudinal and oblique myocardial fiber orientation of the RV free wall compared to the dominant circular mid-wall fibers in the LV lateral wall [6]. Our data are consistent with that reported by Weidemann et al, and methodological differences likely explain the increased strain values that we observed.…”
Section: Discussionsupporting
confidence: 83%
“…Magnetic resonance imaging is the gold standard for assessing RV volumes but its expense limits its current role in the routine bedside assessment of RV function, and exercise magnetic resonance imaging for RV function is currently not well established. Due to the unique myocardial fibre orientation of the RV, base-to-apex longitudinal contraction is considered to be particularly important in RV emptying [24,25]. TAPSE and S′ represent two of the most commonly used, reproducible and validated indices of RV systolic function in clinical practice [19].…”
Section: Discussionmentioning
confidence: 99%